Role of reciprocal changes in predicting short term prognosis of patients of acute STEMI - Khanna, Mridul; Mahajan, Devinder Singh (International Journal of Advances in Medicine, 2020)
Background: Recent studies indicate that STEMI with reciprocal changes is associated with more myocardial area at risk, larger infarct size and less ejection fraction as compared to STEMI without reciprocal changes. We undertook this study for correlating clinical outcome and complications in patients with and without reciprocal changes in ECG in acute STEMI. Methods: Eighty patients were divided into two groups of forty each. One having reciprocal changes in ECG and one without reciprocal changes. The KILLIP class of each patient at time of admission was noted. Patients were monitored for development of any complication, Left ventricular ejection fraction (LVEF) and mortality. BNP levels, Trop I levels, Hba1c levels were obtained at time of admission. Echocardiography was done on the second day of the admission. Results: The patients with reciprocal changes were found to be having a higher KILLIP class on admission. The LVEF of patients with reciprocal changes and who subsequently went on to develop complications was lower than those without reciprocal changes. The number of patients having unsuccessful thrombolysis was significantly higher in the group with reciprocal changes. Conclusions: There was significant association of reciprocal changes in ECG with higher Hba1c, higher KILLIP class and higher incidence of unsuccessful thrombolysis. Moreover, the sensitivity of other markers of poor clinical outcomes, such as BNP and LVEF increases in patients having reciprocal changes in their ECG. The monitoring in such patients should thus be more intensive.